Sudden Unexplained Infant Deaths: New Study Findings Related to Day of Life. Issue 3 (May 2020) - Beal, Judy A.
Abstract : New data on classification and risk factors for sudden unexplained infant deaths based on age of infants at death have been published. Our pediatric nursing expert, Dr. Beal, explains the study findings and how they can help nurses promote safe infant sleep.